Letter (copy) - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
C02-0106-001 4, Aberdare Gardens, Hampstead, LONDON, N.W.6. 21st October, 1937. Mr. G. Jeger, Spanish Medical Aid Committee, 24/28, New Oxford Street, LONDON, W.C.2. Dear Jeger, I am sending you herewith the accounts for the Surgical Goods and Beds bought at the two Sales, with the Catalogue from Stevens. You already have a catalogue of the Sale at Park Lane Hospital. I would like you to attach the accounts to the catalogue, so that reference can be made from the numbers on the accounts to the items in the catalogue. The details of the accounts are as follows:- Stevens Aucton Rooms £12. 5 0. Seville & Sons re Park Lane 58. 17. 0. One Removal Account (enclosed) 2. 17. 0. Another Removal Account, not yet to hand, for removal of the goods from Stevens 12. 0. Commission for buying to the various Buyers 3. 11. 0. Tips re removal of goods actually in house apart from transport 10. 0. Making a total of £78. 12. 0. If you can favour me with your cheque at your convenience I will be obliged. Yours faithfully, 3 Accounts. 1 Catalogue. 292C/946/2/106